التمويل العقاري في مصرف الراجحي في ماليزيا: دراسة فقهية تقويمية = Home-financing in bank Rajihi Malaysia: a evaluative juristic study - Ahmad, Shabir Ahmad Molavi; Arif, Arif Ali; Zakariyah, Habeebullah (Sakarya Universitesi, Turkey, 2020)
تجنبًا للربا أو الغرر أو المحظورات الشرعية الأخرى، فإن مصرف الراجحي بماليزيا قد اعتمد على مخارج شرعية متعددة في التمويل العقاري؛ غير أن هذه المخارج جُوبهت بانتقادات من قبل بعض العلماء والباحثين لكونها تشتمل على محظورات شرعية، بينما يرى الآخرون خلوّها من تلك المحظورات وكونها متوافقة مع ضوابط المخارج الشرعية. وهذا البحث يهدف إلى الوقوف على حقيقة تلك المخارج الشرعية المعتمدة من قبل مصرف الراجحي في ماليزيا في التمويل العقاري وتقويمها لبيان مدى انضباطها بالضوابط الشرعية. وذلك من خلال وصف عام للتمويلات العقارية في المصرف، وآلية الحصول على التمويل العقاري، وبيان المخارج الشرعية المعتمدة فيها مع التحليل والتقويم لتلك المخارج، ثم اقتراح بدائل ومخارج شرعية أكثر انضباطًا بالضوابط الشرعية. وقد توصل البحث إلى أن مصرف الراجحي بماليزيا يُقدّم تمويلات عقارية متعددة، طويلة الآجال بأسعار ثابتة أو غير ثابتة، على أساس مخرج البيع بالثمن الآجل عن طريق مرابحة السلع (التورق) بواسطة بورصة سوق السلع الماليزية (في الغالب)، وأن هذا المخرج القائم على التورق المصرفي عن طريق بورصة سوق السلع وإن كان أفضل من كثير عمليات التورق المصرفية الرائجة في العالم، إلا أنه قد لا يكون مخرجًا شرعيًّا منضبطًا بجميع ضوابط المخارج الشرعية، وكذلك فإن المخرج الذي اعتمده المصرف في رفع إشكالية تمويل طويل الأجل، قد يلزم منه المرابحة بربح متغير في حدود معينة؛ وقد يترتب عليه الغرر الفاحش الذي قد يؤدي إلى النزاع أو شعور العميل بالغبن، والإبراء كأنه منصوص عليه في العقد؛ أي أنه باتفاق مسبق بين العميل والمصرف، وهو ممنوع باتفاق العلماء. فالمخارج المعتمدة في التمويل العقاري في مصرف الراجحي لا يخلو عن بعض الملاحظات الشرعية، ويوجد للتمويل العقاري بدائل ومخارج شرعية أخرى أكثر انضباطًا بالضوابط الشرعية وأوفق للمقاصد الشرعية؛ وهي المشاركة والمشاركة المتناقصة والاستصناع والمرابحة للآمر بالشراء وغيرها.... In order to avoid riba, gharar and other prohibited Shariah elements, al Rajhi Bank Malaysia has adopted several Shariah alternatives to real estate financing. However, these alternatives are not devoid of criticism from scholars and researchers for their being comprised of some prohibited elements, whereas other players see them to be free from these elements, and therefore regard them to be in consonance with the parameters of Shariah alternatives. This study aims to examine and evaluate the essence of these Shariah alternatives employed by al-Rajhi Bank Malaysia for real estate financing in order to understand their level of compliance with Shariah parameters. To do this, a general overview of real estate financing in banks is presented, the mechanism for securing mortgaged is discussed, and the Shariah alternatives used are highlighted, analysed and evaluated, while putting forward a proposition for alternatives that are more in agreement with Shariah parameters. This investigation concludes that al-Rajhi Bank Malaysia offers long-term real estate financing at fixed and floating rates, on the basis of deferred payment sale through commodity murabahah, otherwise known as tawarruq, transacted mostly on Malaysia’s Bursa Suq al-Sila’ platform. Even though this alternative which is based on banking tawarruq as traded on Bursa Suq al-Sila’ is much better than other common banking tawarruq mechanisms around the world, it may not be a viable alternative that complies with all the provisions of Shariah parameters. Moreover, the alternative adopted by the bank to address the issue of long-term financing could involve a murabahah contract with variable profit within particular limits, just as it could also involve excessive gharar, which may lead to a dispute, or the customer to feel being cheated, or getting a rebate as though this is stipulated in the contract. This is forbidden according to the unanimous agreement of scholars. The alternatives employed for real estate financing in al-Rajhi Bank is not totally devoid of Shariah issues. There are other alternative real estate financing products that are much more compliant with Shariah parameters and more in line with the objectives of Shariah. These are musharakah, diminishing musharakah, istisna’ murabahah for the purchase order, among many other models